Prospective Assessment of Prescribing Pattern of Intravenous Proton Pump Inhibitors in an Indian Tertiary-Care Teaching Hospital - Churi, Shobha; Jogani, Arun (Indian Journal of Pharmacy Practice)
Context: Inappropriate use of intravenous proton pump inhibitors (IV PPIs) has been a major challenge for private health-care setups. Inappropriate prescribing may result in increased shortages of IV PPIs in hospitals, therapeutic burden, adverse effects, and treatment costs. Therefore, the study was sought to determine drug utilization patterns (appropriateness and inappropriateness) of IV PPIs in an Indian tertiary-care teaching hospital. Aims: To assess the drug utilization pattern of IV PPIs in a tertiary-care teaching hospital. Settings and Design: This was a prospective observational study. Methods and Material: This study was conducted over a period of one month. Patients who were ≥18 years of age, who were admitted in the internal medicine, surgery, or gastroenterology wards, and who were receiving IV PPIs were included in the study. Paediatric patients and outpatients were not enrolled in the study. Ddemographics, past medication and surgery, current medical condition and medication, dose, dosing interval, duration of therapy, length of stay, and endoscopic details of each patient was collected from patients' case notes, treatment charts, and laboratory/diagnostic test reports, and evaluated for appropriateness regarding indication. Statistical analysis: Chi square test (χ2) was used to analyze the data. Results: Prospective assessment involved 611 patients over a 1-month period. For prophylaxis (stress ulcer, pre-operative and post- operative prophylaxis) and treatment, IV PPIs were prescribed inappropriately to 289 (89.2%) internal medicine and 97 (34.04%) surgery ward patients. Prolonged therapy was found in patients who received IV PPIs for stress ulcer prophylaxis. Conclusion: This study revealed significant inappropriateness of PPI administration with particular reference to indication to use, duration of therapy, and changeover of therapy in an Indian tertiary-care teaching hospital.
Keywords: Intravenous proton pump inhibitors; Prescribing pattern; Prospective assessment; Rational drug use; Drug utilization evaluation